Attitudes of Arabic language teachers towards the use of learning through play in teaching children with autism spectrum disorder in Amman - Al-Mashaqbeh, Muhammad Hamid (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the attitudes of Arabic language teachers towards the use of learning through play in teaching children with autism spectrum disorder in Amman and to identify the impact of the following variables (gender, educational qualification, years of experience). It was distributed to (50) teachers of the Arabic language, and its validity and reliability were confirmed by a committee of arbitrators from specialists. The Arabic language teachers towards the use of learning through play in teaching children with autism spectrum disorder was significant, as it was found that there were no statistically significant differences at the level of significance (α ≤ 0.05) between the average responses of the study sample members towards trends. Arabic language teachers towards the use of learning by playing in teaching children autism spectrum disorder due to the gender variable (gender, educational qualification, years of experience) and based on the results of this study, the researcher recommended recommendations, the most important of which is the need to work on integrating autistic children into the family Educational games as it increases their motivation, interest in developing learning through play for children with autism as much as possible, the need to work on using the method of play in developing communication skill for children on the autism spectrum.
Keywords: Attitudes; Arabic language teachers; learning by playing; autism spectrum disorder